College Algebra / Third Edition - Barnett Raymond A. (Mcgraw Hill Book Company, 1987)
Preface, Basic Algebraic Operations: A Review, Equations and Inequalities, Graphs and Functions, Polynomial Functions and Theory of Equations, Exponential and Logarithmic Functions, Systems of Equations and Inequalities, Matrices and Determinants, Sequences and Series, An Introduction to Probability, Appendix A: Significant Digits, Tables, Answers, Index.